Roles of p300 and cyclic adenosine monophosphate response element binding protein in high glucose‐induced hypoxia‐inducible factor 1α inactivation under hypoxic conditions. Issue 3 (24th January 2017) - Ding, Lingtao; Yang, Minlie; Zhao, Tianlan; Lv, Guozhong
Abstract : Both p300 and CREB are required for the function integrity of HIF‐1α mediated VEGF transcription and subsequent angiogenesis, suggesting future studies to improve burning wound healing may be directed to optimization of the interaction between p300, CREB and HIF‐1α. Abstract: Aims/Introduction: Given the high prevalence of diabetes and burn injuries worldwide, it is essential to dissect the underlying mechanism of delayed burn wound healing in diabetes patients, especially the high glucose‐induced hypoxia‐inducible factor 1 (HIF‐1)‐mediated transcription defects. Materials and Methods: Human umbilical vein endothelial cells were cultured with low or high concentrations of glucose. HIF‐1α‐induced vascular endothelial growth factor (VEGF) transcription was measured by luciferase assay. Immunofluorescence staining was carried out to visualize cyclic adenosine monophosphate response element binding protein (CREB) localization. Immunoprecipitation was carried out to characterize the association between HIF‐1α/p300/CREB. To test whether p300, CREB or p300+CREB co‐overexpression was sufficient to rescue the HIF‐1‐mediated transcription defect after high glucose exposure, p300, CREB or p300+CREB co‐overexpression were engineered, and VEGF expression was quantified. Finally, in vitro angiogenesis assay was carried out to test whether the high glucose‐induced angiogenesis defect is rescuable by p300 and CREB co‐overexpression. Results: Chronic high glucose treatment resulted in impaired HIF‐1‐induced VEGF transcription and CREB exclusion from the nucleus. P300 or CREB overexpression alone cannot rescue high glucose‐induced HIF‐1α transcription defects. In contrast, co‐overexpression of p300 and CREB dramatically ameliorated high glucose‐induced impairment of HIF‐1‐mediated VEGF transcription, as well as in vitro angiogenesis. Finally, we showed that co‐overexpression of p300 and CREB rectifies the dissociation of HIF‐1α‐p300‐CREB protein complex in chronic high glucose‐treated cells. Conclusion: Both p300 and CREB are required for the function integrity of HIF‐1α transcription machinery and subsequent angiogenesis, suggesting future studies to improve burn wound healing might be directed to optimization of the interaction between p300, CREB and HIF‐1α.